Hydro-geomorphological and sedimentological processes along the major fluvial-lacustrine delta of the Paraná River (Argentina): Their role in floodplain construction - Dominguez Ruben, Lucas Gerardo (2023)
River-dominated sea deltas have been thoroughly studied by different authors. In these environments the interrelationships of the hydro-sedimentological variables between river, tides, and waves, among others, are the main factors controlling the delta formation. However, few studies have focused on the deltaic processes in river–lagoon environments and even fewer in large river floodplains (defined here as a fluvial-lacustrine delta, FLD) and their role in floodplain construction. This study provides a comprehensive and novel analysis approach combining satellite imagery treatment and aerial photographs with detailed field measurements of sediment samplers, cores, and acoustic techniques applied to quantify flow and discharge distribution along main, secondary, floodplain channels, and lagoon systems under different hydro-sedimentological conditions. All data allow a full description of deltaic processes and the main variables that control the evolution of the major FLD located along the Middle Paraná River floodplain (Argentina). These results show: (i) pre-existing local geology elements affect the deltaic processes; (ii) the hydro-sedimentological behaviour of the main channel and its connection with the floodplain channels and independent basin systems affects the delta evolution; (iii) the dynamics (temporally and spatially) of sediment transport input and the interaction with lagoons produce different delta front bars planform and composition; (iv) periods of mean and high water levels play a key role in delta evolution; and (v) the rapid vegetation growth above the formed bars favours the sedimentation of fine material, producing permanent changes and leading to floodplain construction. Particularly, our findings suggest a complex interrelationship between the different factors in this particular environment, such as hydrology, local geology, main/secondary and floodplain channels, sediment supply, sediment transport modes, vegetation, and free surface slopes. All these factors act together in a complex manner, providing unique features to the FLD system that could help us better understand the floodplains construction in large river systems worldwide.